2009
DOI: 10.3402/gha.v2i0.2017
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of alcohol consumption in diverse rural populations in the Asian region

Abstract: BackgroundAlcohol abuse, together with tobacco use, is a major determinant of health and social well-being, and is one of the most important of 26 risk factors comparatively assessed in low and middle income countries, surpassed only by high blood pressure and tobacco.ObjectivesThe alcohol consumption patterns and the associations between consumption of alcohol and socio-demographic and cultural factors have been investigated in nine rural Health and Demographic Surveillance System (HDSS) located in five Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 9 publications
0
21
3
1
Order By: Relevance
“…Kestila and colleagues,11 in a nationally representative study of young adults in Finland, reported a significant association between a low level of education and heavy alcohol use. In a similar study carried out in rural Asian populations, Bich and colleagues reported an association between alcohol use and failure to attend or complete primary education 12. The evidence of association in our study is, however, weak as respondents’ level of education was not an independent predictor of both forms of alcohol use.…”
Section: Discussioncontrasting
confidence: 78%
“…Kestila and colleagues,11 in a nationally representative study of young adults in Finland, reported a significant association between a low level of education and heavy alcohol use. In a similar study carried out in rural Asian populations, Bich and colleagues reported an association between alcohol use and failure to attend or complete primary education 12. The evidence of association in our study is, however, weak as respondents’ level of education was not an independent predictor of both forms of alcohol use.…”
Section: Discussioncontrasting
confidence: 78%
“…On average around 40% of all studies included some sort of socioeconomic indicator mirroring educational attainment [15, 17, 21–24, 32, 34, 35, 37–40, 4244, 47, 48, 50, 55, 56, 60, 63, 66, 68, 69, 71, 73, 75, 76, 79, 81, 83–85, 91, 92, 95, 99, 101, 102, 104108, 111, 112, 114, 122, 123, 125–127, 129, 131, 133, 135–138, 140, 142, 155, 156], income or wealth [15, 17, 2022, 25, 28, 37, 39, 43, 47, 52, 55, 56, 60, 63, 66, …”
Section: Resultsmentioning
confidence: 99%
“…HIV risk reduction interventions with IDU may need to explore the potential role of alcohol use and abuse and may want to review with IDU specific strategies to limit alcohol consumption including spacing drinks, alternating alcoholic drinks with nonalcoholic beverages, setting a limit on consumption, or finding alternative activities that do not include substance use, such as sports (Benton, et al, 2004; Delva, et al, 2004; Glassman, Werch, & Jobli, 2007; Martens, Ferrier, & Cimini, 2007; Martens, Pederson, Labrie, Ferrier, & Cimini, 2007; Martens, et al, 2004; Sugarman & Carey, 2007). Like many developing countries, information about alcohol abuse and alcohol consumption-related problems is less pervasive in Vietnam (Huu Bich, et al, 2009). Programs that target male IDU should increase awareness of the direct (e.g., liver disease, accidents, violence, psychiatric conditions, and interpersonal conflict) and indirect (e.g., increased sexual risk behaviors, increasing risk to overdose from mixing alcohol with heroin) harms associated with alcohol use.…”
Section: Discussionmentioning
confidence: 99%